Newly identified c-di-GMP pathway putative EAL domain gene STM0343 regulates stress resistance and virulence in Salmonella enterica serovar Typhimurium - Kaifeng Chen; Lili Li; Nanwei Wang; Zhouping Zhou; Peng Pan; Chenggang Xu; Dage Sun; Jiayi Li; Changzhi Dai; Dai Kuang; Ming Liao; Jianmin Zhang (Veterinary Research)
Abstract S. Typhimurium is a significant zoonotic pathogen, and its survival and transmission rely on stress resistance and virulence factors. Therefore, identifying key regulatory elements is crucial for preventing and controlling S. Typhimurium. We performed transcriptomic analysis and screened for a c-di-GMP pathway key gene STM0343, a putative EAL domain protein with an unknown function. Our findings revealed that the deletion of this gene (269ΔSTM0343) led to a 29.85% increase in c-di-GMP. In terms of stress resistance, the strain 269ΔSTM0343 showed significant improvements compared to the wild strain WT269. Specifically, it exhibited increases of 95.74% in extracellular protein and 35.96% in exopolysaccharide production by upregulating the expression of relevant genes. As a result, the biofilm formation ability of 269ΔSTM0343 was enhanced by 21.54%, accompanied by a more pronounced red, dry, and rough colony morphology. 269ΔSTM0343 also showed a 19.03% decrease in motility due to the downregulation of flhD expression. As a result, 269ΔSTM0343 increased resistance to various antibiotics, as well as to acidic conditions, oxidative stress, and disinfectants. In terms of virulence, compared to WT269, the adhesion and invasive ability of 269ΔSTM0343 to HeLa cells was enhanced by onefold and 25.67%, respectively. In in vivo experiments, mice challenged with 269ΔSTM0343 experienced greater weight loss, and the bacterial loads in the spleen, liver, and intestines were elevated by fivefold, 30-fold, and 21-fold, respectively, accompanied by more severe pathological damage. Mechanistic studies revealed that the adhesion and invasion capacities of 269ΔSTM0343ΔCsgB decreased by 29.41% and 68.58%, respectively, compared to 269ΔSTM0343. Additionally, LacZ gene reporting indicated that STM0343 inhibited the expression of CsgB. This suggests that STM0343 suppresses virulence by downregulating CsgB expression. This study provides insights into the regulatory mechanisms by which STM0343 reduces the stress resistance and pathogenicity of S. Typhimurium.